Physiological and Molecular Characteristics of Bacterial Isolates from Bandealit Coastal Area Jember, East Java, Indonesia - DINA FITRIYAH; SATTYA ARIMURTI; KARTIKA SENJARINI (HAYATI Journal of Biosciences, 2013)
Bacteria are the most dominant group of microorganisms in aquatic environments due to their role in organic matter decomposition. Decomposition activity is related to the type  and dominance of bacteria in the communities. Therefore, study of bacterial diversity is an important step to understand their role in aquatic ecosystems. This study was to determine bacterial diversity and their physiological characters of bacteria from Bandealit Coast in Jember East Java Indonesia. The bacteria were confirmed by BOX-PCR profile for their genetic polymorphisms. Identification of potential isolate was conducted based on 16S rRNA gene sequence. The result showed that BA011109 isolate was able to utilize D-cellobiose as a sole substrate, indicating its ability to hydrolyse b-glucoside bond. This isolate was a potential decomposer in the area considering that most of organic pollutants were from plants that cointain high cellulose. Based on its 16S rRNA gene sequence, this isolate was closely related to Microbacterium esteraromaticum with 100% homology. Further study on quantitative hydrolytic activities is needed to elucidate its role as an organic matter decomposer in aquatic environment.